2004
DOI: 10.1590/s1516-35982004000200011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de modelos para estimação de componentes de (co)variância em características de desempenho e reprodutivas em suínos

Abstract: RESUMO -Foram analisados dados de características de desempenho e reprodutivas de suínos de uma linha em desenvolvimento da raça Large White, para verificar a importância da inclusão dos efeitos materno e comum de leitegada nos modelos de avaliação genética animal, utilizando quatro diferentes modelos: modelo 1 -efeito genético aditivo direto; modelo 2 -efeito genético aditivo direto e materno; modelo 3 -efeito genético aditivo direto e comum de leitegada; e modelo 4 -efeito genético aditivo direto e materno e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
2
2
1
Order By: Relevance
“…A mean value lower than the one found in the present study was reported by Torres Filho et al (2004), who found a mean of 318.56 days in animals of the Large White breed. This difference may be due to the fact that this study was performed with commercial herds, for which each breeder determines in his own way the best time to have his sows mated.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…A mean value lower than the one found in the present study was reported by Torres Filho et al (2004), who found a mean of 318.56 days in animals of the Large White breed. This difference may be due to the fact that this study was performed with commercial herds, for which each breeder determines in his own way the best time to have his sows mated.…”
Section: Discussioncontrasting
confidence: 83%
“…The author considered at the time that this value was rather high. Based on this statement, on the findings of Torres Filho et al (2004) and on the results obtained in this study, we suggest that there has been genetic progress and/or environmental improvement regarding this trait in Brazil.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The heritability estimates found in this study using the L1 and L2 models based on 120 markers with the largest effects agree with those obtained by Torres Filho et al (2004), who reported values of between 0.13 and 0.20 for age until achieving 100 kg in Large White pigs. For the models S1 and S2, the heritability was calculated using Equation 11, with the error variance replaced by 1 / (1 -c), where c is the proportion of censored data.…”
Section: Discussionsupporting
confidence: 91%
“…According to Torres Filho et al (2004), the most suitable model for evaluating the performance traits and DAFF includes the direct genetic effect of the animal, the maternal effect and the litter common effect. For litter traits, the most suitable model includes only the direct genetic effect of the animal.…”
Section: Methodsmentioning
confidence: 99%